Theses and dissertations in institutional repositories: an Asian perspective. Issue 9 (29th August 2014) - Ahmed, Aquil; Alreyaee, Sulaiman; Rahman, Azizur
Abstract : Purpose: Institutional Repositories constitute an integral part of present day digital libraries allowing global access to scholarly publications and provides an opportunity for future research enhancement and long term preservation of information. Electronic Theses and Dissertations (ETDs) represent a growing segment of available content in institutional repositories where they contribute to the impact and ranking of their institutions. The present study traces the growth and development of online E-theses repositories in Asia within the broader framework of open access. Design/methodology/approach: The present study tries to discover the composition of ETD repositories in Asia based on the 7 key parameters i.e. country, types, language, disciplines, software, content types and repository policies. In order to achieve the stated objectives, the ETD repositories developed by Asian countries were identified by selecting the database of OpenDOAR (Directory of Open Access Repositories) and the retrieved data were thoroughly analyzed for the necessary information. Findings: Theses and dissertations are considered an important part of information resources in any institution. They are often the only source of research work. Unfortunately, access to these valuable unpublished resources is often restricted to parent institution only. The authors found that ETD repositories are addressing this problem by making institutional knowledge available online and thereby not only increasing its visibility and use but making them contribute to the impact and ranking of their institutions. Asian countries are beginning to embrace the idea of digitizing, archiving and making their theses and dissertations available online. The study found that more than half of all IRs listed in the directory of OpenDOAR contain ETDs. ETD system is growing fast in some Asian countries. However, the number of universities having E-theses repositories is meagre considering the large number of quality academic and research institutions across Asian countries. Practical implications: The paper argues that ETD repositories not only benefit students and institutions by enhancing education, expanding research, but increasing a university's visibility and use and thereby contributing to the impact and ranking of its parent institutions. Originality/value: The study hopes to heighten awareness of research being conducted in Asia and its contribution to a global knowledge base. Some of the suggestions to improve the existing conditions and strengthen the growth rate of ETDs in Asia are also presented.